CMC-citric acid Cu(II) cross-linked binder approach to improve the electrochemical performance of Si-based electrodes. (1st May 2019) - Mazouzi, D.; Grissa, R.; Paris, M.; Karkar, Z.; Huet, L.; Guyomard, D.; Roué, L.; Devic, T.; Lestriez, B.
Abstract: Maturation, which consists of storing the electrode under humid atmosphere before drying and cell assembly, improves very significantly the cyclability of silicon-based composite electrodes made with an acidic binder. During maturation, the atmospheric-induced corrosion of the current collector releases oxidized copper species that migrate into the electrode to physically crosslink the binder phase, substantially modifying its resiliency to the silicon volume variation. The pre-addition of a small amount of copper salt in the electrode slurry allows to reach similar improvement of electrochemical performance than maturation.